2000
DOI: 10.1016/s0022-2275(20)31981-7
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of the propeptide of apolipoprotein A-I reduces protein expression but stimulates effective conversion of preβ-high density lipoprotein to α-high density lipoprotein

Abstract: The properties of the mature and pro-forms of recombinant apolipoprotein A-I (apoA-I) were compared with those of apoA-I isolated from human plasma. When the synthesis and secretion of pro-and mature forms of apoA-I from a baculovirus/insect cell expression system were compared in parallel experiments, the amount of the pro-form of apoA-I synthesized and secreted was severalfold higher than that of the mature form of apoA-I. A comparison of the properties of the pro-and mature forms of recombinant apoA-I and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…We (4,5) and others (6) have demonstrated that expression of recombinant apoA-I with the pro-peptide deleted impairs secretion and decreases the overall efficiency of the expression of apoA-I, suggesting that apoA-I is synthesized as a pro-protein to aid in intracellular transport of the protein through the cellular apparatus. We have also demonstrated that the presence of pro-peptide impairs interconversion of preβ-HDL into R-HDL (5), suggesting a requirement for its cleavage. An apoA-I(P3R) substitution has been recorded, in which the individual was found to have a proapoA-I concentration of the variant protein approximately 3 times the level of the normal protein; however, no detectable disease state was recognizable with this mutation (7).…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…We (4,5) and others (6) have demonstrated that expression of recombinant apoA-I with the pro-peptide deleted impairs secretion and decreases the overall efficiency of the expression of apoA-I, suggesting that apoA-I is synthesized as a pro-protein to aid in intracellular transport of the protein through the cellular apparatus. We have also demonstrated that the presence of pro-peptide impairs interconversion of preβ-HDL into R-HDL (5), suggesting a requirement for its cleavage. An apoA-I(P3R) substitution has been recorded, in which the individual was found to have a proapoA-I concentration of the variant protein approximately 3 times the level of the normal protein; however, no detectable disease state was recognizable with this mutation (7).…”
mentioning
confidence: 92%
“…The functional role of the pro-peptide, the requirement for its subsequent cleavage, and the structural features essential for this cleavage are unclear. We ( , ) and others () have demonstrated that expression of recombinant apoA-I with the pro-peptide deleted impairs secretion and decreases the overall efficiency of the expression of apoA-I, suggesting that apoA-I is synthesized as a pro-protein to aid in intracellular transport of the protein through the cellular apparatus. We have also demonstrated that the presence of pro-peptide impairs interconversion of preβ-HDL into α-HDL (), suggesting a requirement for its cleavage.…”
mentioning
confidence: 92%
“…LDL was purified from human plasma by sequential centrifugation and acetylated as described by Basu et al [53]. Cholesterol and phospholipid efflux were assessed as described previously [54]. Briefly, fibroblasts were incubated in labeling medium containing [ 3 H]cholesterol (75 kBq/ml) or [methyl- 14 C] choline (0.2 MBq/ml) for 48 hours.…”
Section: Lipid Efflux Assaysmentioning
confidence: 99%